Perspectivas sobre a saúde mental em Portugal - Palha, João (2017)
The Portuguese National Mental Health Plan, approved for the period between 2007-2016 has created expectations for the improvement of the quality of care in the domains that have not been achieved. This article will briefly discuss three key aspects regarding the Portuguese situation in the mental health field: access to care; mental health services; stigma and literacy in mental health. In order to contextualize these issues, the article starts by defining mental health and mental illness, and by highlighting its prevalence and burden associated.